Improving market information systems to inform policymaking - Glauber, Joseph W. (2023)
Joseph Glauber IFPRI-AMIS SEMINAR SERIES Facilitating Anticipatory Action with Improved Early Warning Guidance Co-organized by IFPRI and Agricultural Market Information System (AMIS) SEP 26, 2023 - 9:00 TO 10:30AM EDT